Effects of Nosema ceranae and thiametoxam in Apis mellifera: A comparative study in Africanized and Carniolan honey bees - Gregorc, Ales; Silva-Zacarin, Elaine C.M.; Carvalho, Stephan Malfitano; Kramberger, Doris; Teixeira, Erica W.; Malaspina, Osmar [UNESP] (Elsevier, 2016)
Multiple stressors, such as chemicals and pathogens, are likely to be detrimental for the health and lifespan of Apis mellifera, a bee species frequently exposed to both factors in the field and inside hives. The main objective of the present study was to evaluate comparatively the health of Carniolan and Africanized honey bees (AHB) co-exposed to thiamethoxam and Nosema ceranae (N. ceranae) spores. Newly-emerged worker honey bees were exposed solely with different sublethal doses of thiamethoxam (2% and 0.2% of LD50 for AHB), which could be consumed by bees under field conditions. Toxicity tests for the Carniolan bees were performed, and the LD50 of thiamethoxam for Carniolan honey bees was 7.86 ng bee-1. Immunohistological analyses were also performed to detect cell death in the midgut of thiamethoxam and/or N. ceranae treated bees. Thiamethoxam exposure had no negative impact on Nosema development in experimental conditions, but it clearly inhibited cell death in the midgut of thiamethoxam and Nosema-exposed bees, as demonstrated by immunohistochemical data. Indeed, thiamethoxam exposure only had a minor synergistic toxic effect on midgut tissue when applied as a low dose simultaneously with N. ceranae to AHB and Carniolan honey bees, in comparison with the effect caused by both stressors separately. Our data provides insights into the effects of the neonicotenoid thiamethoxam on the AHB and Carniolan honey bee life span, as well as the effects of simultaneous application of thiamethoxam and N. ceranae spores to honey bees.
Keywords: Cell death; Midgut; Neonicotinoid; Pathogen; Worker honey bee